GERAKAN PEDULI SAMPAH SEBAGAI UPAYA PENINGKATAN EKONOMI PADA MASA PANDEMI COVID-19 DI DESA BLULUKAN COLOMADU KARANGANYAR - Susilo Surahman; Muhammad Julijanto; Nurul Huda; Sigit Arif Bowo (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The Covid-19 pandemic is closely related to the healthy living culture established through the New Habit Adaptation program. This research is a type of quantitative research. The purpose of this study is to find out the influence of the waste care movement with economic improvement. This research is a type of quantitative research with quasi-experimental approach. The research was conducted in Blulukan Colomadu Karanganyar Village. The sample in this study numbered 50 random citizens, with the division of 25 people as a control group, and 25 people as an experimental group. The results showed that globally it can be concluded that the economic improvement of the respondents in this study was at a score of 105 with a standard deviation of 11.46, which means the level of economic improvement is in the moderate or sufficient category.